1996
DOI: 10.1074/jbc.271.47.29958
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of the CLK1 Gene Product, a Novel CaM Kinase-like Protein Kinase from the Yeast Saccharomyces cerevisiae

Abstract: The CLK1 gene of Saccharomyces cerevisiae encodes a 610-residue protein kinase that resembles known type II Ca 2؉ /calmodulin-dependent protein kinases (CaM kinases), including the CMK1 and CMK2 gene products from the same yeast. The Clk1 kinase domain is preceded by a 162-residue N-terminal extension, followed by a 132-residue C-terminal extension (which contains a basic segment resembling known calmodulin-binding sites) and is as similar to mammalian CaM kinase (38% identity to rat CaM kinase ␣) as it is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
51
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 62 publications
6
51
0
Order By: Relevance
“…2, a computer-based amino acid sequence comparison revealed that the greatest degree of amino acid sequence identity was shared with fission yeast Cmk2 (39%), and budding yeast Rck2/Clk1 (32%) (26). The kinase domains in all of these proteins share significant homology with the mammalian Ca 2ϩ /calmodulin kinase superfamily, although the significance of this is unclear as extensive analysis of S. cerevisiae Rck2/Clk1 failed to uncover any regulation by calmodulin (36).…”
Section: Srk1mentioning
confidence: 99%
“…2, a computer-based amino acid sequence comparison revealed that the greatest degree of amino acid sequence identity was shared with fission yeast Cmk2 (39%), and budding yeast Rck2/Clk1 (32%) (26). The kinase domains in all of these proteins share significant homology with the mammalian Ca 2ϩ /calmodulin kinase superfamily, although the significance of this is unclear as extensive analysis of S. cerevisiae Rck2/Clk1 failed to uncover any regulation by calmodulin (36).…”
Section: Srk1mentioning
confidence: 99%
“…Despite their high similarity to Ca 2ϩ ͞calmodulin-dependent kinases, Rck2 does not respond to Ca 2ϩ signals, and its regulatory inputs have remained unknown (12). The kinases were also discovered serendipitously by complementation of Schizosaccharomyces pombe mutants deficient in the DNA damage pathway (13).…”
mentioning
confidence: 96%
“…In the set of positive clones (Table 1), we found independent fusions containing sequences of the following three genes: RCK2, GLO3, and RNR4. Rck2 has been previously identified as a Ser͞Thr protein kinase (12,13). Glo3 is thought to act as GTPase-activating protein for ADP ribosylation factor Arf1, which is involved in vesicular transport (23).…”
Section: Hog1mentioning
confidence: 99%
See 1 more Smart Citation
“…cmk2 was isolated by its sequence similarity to the yeast and mammalian calmodulin kinases. 2 It has a high degree of homology to budding yeast RCK2, previously isolated by virtue of its sequence similarity to mammalian calmodulin kinases (30). It has also been described as a suppressor of fission yeast checkpoint mutants (31) and a substrate of Hog1, the MAPK in budding yeast responsive only to osmolarity stress (32).…”
mentioning
confidence: 99%